Unveiling the effect of transport infrastructure and technological innovation on economic growth, energy consumption and CO2 emissions - Acheampong, A.O.; Dzator, J.; Dzator, M.; Salim, Ruhul (ELSEVIER SCIENCE INC, 2022)
This study investigates the impact of transport infrastructure and technological innovation on economic growth (GDP), energy consumption (EC) and carbon emissions (CO2e) in the European Union (EU) using the dynamic system-generalised method of moment and data from 1995 to 2019. The results indicate that EC unidirectionally increases GDP, while GDP and EC reduce and increase CO2e, respectively. The results also demonstrate that innovation directly increases GDP and EC; however, freight transport infrastructure increases GDP and CO2e while reducing EC. The nonlinear analysis reveals that innovation has a U-shaped relationship with GDP and an inverted U-shaped relationship with EC. Furthermore, our results demonstrate that freight and rail infrastructure have an inverted U-shaped relationship with CO2e and no nonlinear relationship with GDP. Again, the rail infrastructure has a U-shaped relationship with EC. The conditional effect analysis reveals that freight and rail infrastructure interact with innovation to raise GDP. The findings indicate that freight transport infrastructure interacts with innovation to reduce EC and CO2e. Finally, rail and freight infrastructure interact with trade and foreign direct investment to influence GDP, EC and CO2e. Subsequently, EU countries must emphasise and enhance technological innovation to achieve energy efficiency.